Spread of pathological tau proteins through communicating neurons in human Alzheimer's disease - Jacob W. Vogel (Nature Portfolio, 2020)
The tau protein is theorized to spread transneuronally in Alzheimers disease, though this theory remains unproven in humans. Our simulations of epidemic-like protein spreading across human brain networks support this theory, and suggest the spreading dynamics are modified by β-amyloid